Implementasi Peran Manajerial Kepala Sekolah di Tk Fastrack Fun School dan Tk Rumah Citta - Tri Nugroho (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2014)
The Implementation of The Managerial Roles of The principals of Fastrack Fun School and Rumah Citta Kindergarten.The aim of this research is to reveal the implementation of the managerial roles of the principals of Fastrack Fun School and Rumah Citta kindergarten in (1) school programs, (2) school potentials, (3) activating school personnel and (4) school personnel work accomplishment. This research used the qualitative approach. The subjects consist of principals, teachers and employees. The data were collected through observations, interviews and documents. The data analysis used a triangulation methodology. In this research, the interview with the principals was triangulated with the result of the interview with the teachers and employees. The result of this research reveals that the principal of Fastrack Fun School and Rumah Citta Kindergarten plan the school program, including the Sentra and renstop involving teachers and employees. The principals organize the staff in which they can work in their field and potentials, so they can work without overlapping activities, and with specific job descriptions and good coordination so they can achieve the school goals. The principals activate commanding the employees by advising and directing intensively regularly in order to make them work correctly according to the goals. These principals evaluate and conduct the employees in order to make them work and achieve their goals.